Pengaruh Pemahaman Wajib Pajak dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak - Muhammad Judhanto Eka Bio; Nanang Suryadi (ECONBANK: Journal of Economics and Banking, 2021)
The aim is to determine the effect of taxpayer understanding and service quality on taxpayer compliance at KPP Pratama Gresik Selatan. This type of research is explanatory research which explains and proves the influence between variables through hypothesis testing. The sampling technique used random sample sampling with a sample size of 97 taxpayers who do reporting and tax payments located in South Gresik. Data analysis using multiple linear regression analysis. The results of this study indicate that the variables of taxpayer understanding, physical evidence, reliability, responsiveness, assurance and empathy have a positive and significant effect on taxpayer compliance. Physical evidence variable has the most dominant influence on taxpayer compliance